Availability and utilization of feed resources in small ruminant production among smallholder farmers in northern Ghana - Konlan, Solomon Pigangsoa (University for Development Studies, 2018)
An evaluation of feed resource availability, utilization and options for improving efficiency of use was investigated in 2 Surveys and 3 Experiments. The first Survey was an assessment of existing feed resources in a crop-livestock production system for identification of critical seasonal shortages. Focus group discussions involving 150 crop – livestock farmers (108 men 42 women) and individual interviews with semi-structured questionnaires were used in collection of data. The results showed that existing feed resources were natural pasture, crop residues, and agro-industrial by-products. However, few farmers (18%) had stands of browse plants like Leucaena leucocephala, Cajanus cajan and Gliricidia sepium. Grazing of natural pasture provided 80% of annual DM requirement of ruminants and 20% supplemented by farmers with collected natural fodder, crop residues and purchased feed. Feed availability was highest between August and November; and a shortage gap occurred in the dry season which became critical between February and April. The second Survey involved an assessment of emerging feed markets in northern Ghana to determine the types and prices of feedstuffs sold. Data were collected from feed markets in Wa, Bolgatanga and Tamale in Upper West, Upper East and Northern regions respectively. A total of 170 respondents were interviewed for this study. Four categories of feedstuffs: crop residues, agro-industrial by-products (AIBPs), fresh grasses and leaves of local browse plants were found in all the three feed markets surveyed. Price of cowpea haulm was highest (P<0.05) at GHȻ 1.00 /kg DM whereas rice bran was the lowest at GHȻ 0.12 /kg DM. Prices of feedstuffs differed (P<0.05) among markets and were highest (GHȻ 0.58/kg DM) in Bolgatanga market and lowest (GHȻ 0.32/kg DM) in the Wa market. The CP content of feedstuffs had less influence on price variations. The effect of season on quantity and quality of forage in communal pasture was estimated in Experiment I to determine the extent of herbage variations in different seasons observed in Survey I. Data were collected in early dry (Nov-Jan) and late dry (Feb-Apr) seasons, and early wet (May-Jul) and main wet (Aug-Oct) seasons using a 1-m2 wooden quadrat. This Experiment was conducted as a randomized complete block design. The 3 regions were blocked, 3 communities in each region were replicates and 4 seasons as treatments. It included 9 communal pasture fields’ herbage yield estimation, 3 in each region of northern Ghana. Six quadrat samples were taken per field in each season for 4 seasons. Also, residue yields of commonly grown crops were estimated at crop harvest. Herbage yield differed (P<0.05) among seasons. The values were 3.08, 1.71, 0.56 and 2.33 tonnes DM/ha for early dry, late dry, early wet and main wet seasons respectively. Season affected (P<0.05) nutritive quality of pasture. Crude protein content of the commonly grazed forage species differed (P<0.05) among seasons. The values obtained were 75, 45, 174 and 165 g/kg DM for early dry, late dry, early wet and main wet seasons respectively. Estimated crop residue generated as part of the feed resources showed that sorghum residue yield was 8.5 tonnes DM/ha and was highest (P<0.05) whereas cowpea had the lowest value (1.8 tonnes DM/ha). In order to address the low quality and quantity of feedstuff in the pasture, on-farm feed supplementation was investigated in Experiment II. This was to determine the effect of concentrate supplementation plus healthcare and season on the intake and voiding of DM and N and growth performance of sheep in the Northern, Upper East and Upper West regions of Ghana. The experiment was done as a randomized complete block design. Regions were blocked and communities in each region were replicates. A total of 36 smallholder sheep farms with an average of 18.6 ± 8.7 sheep per farmer were selected. The animals in each farm were randomly assigned to one of two feeding regimes as treatments. The treatments were none-concentrate supplementation (control) and application of a combined package of concentrate supplementary feed plus healthcare. Data were collected in each season. Animals on concentrate supplementation plus healthcare had higher (P<0.05) intake of DM (608 g DM/d) than control group (515 g DM/d). Season significantly (P<0.05) affected DM intake. The highest intake of DM was observed during early wet season (679 g DM/d) and lowest in main wet season (397 g DM/d). Faecal output was not affected (P>0.05) by supplementation. Season however, affected (P<0.05) faecal output. Nitrogen (N) intake was affected (P<0.05) by concentrate supplementation. The highest N intake was observed during early wet season (14 g/d) and the lowest in the late dry season (7 g/d). Highest N voiding was found in early wet season (6 g/d) and lowest in late dry season (4 g/d). Average daily gain of 34 g/d was observed in animals on concentrate supplementation plus health care and was higher (P<0.05) than 18 g/d in control group. The N content of faeces was higher in early dry and early wet seasons than in other seasons. Thus faeces could be collected as manure for improving poor soils. Due to the cost of concentrate feed, Experiment III was conducted to further investigate the growth performance of Djallonkè sheep on agro-residues supplementation that require minimal cost. The treatments were non-supplementation (T0), supplementation with sole groundnut haulm (T1), sole maize bran (T2) and combination of T1 and T2 in a ratio of 2:1. These 4 treatments were replicated 3 times in a completely randomized design. The supplementation affected (P<0.05) average daily gain of the animals. The Average daily gains of the various treatments were 21, 32, 31 and 46 g/d for T0, T1, T2 and T3 respectively. Therefore combined supplementation of crop residues and AIBPs improved the performance of sheep.